Reviving Matrix for Nerve Reconstruction in Rabbit Model of Chronic Peripheral Nerve Injury With Massive Loss Defect - Rochkind, Shimon; Almog, Mara; Meilin, Sigal; Nevo, Zvi (Frontiers in Surgery, 2021)
Background and Aims: The aim of this study was to investigate the innovative guiding regenerative gel (GRG) and antigliotic GRG (AGRG) fillings for nerve conduits, prepared with Food and Drug Administration (FDA)-approved agents and expected to provide an alternative to autologous nerve graft and to enable reconnection of massive nerve gaps in a rabbit model of chronic peripheral nerve injury with massive loss defect that simulates the human condition of chronic injury with a large gap. Methods: The components and dosimetry for GRG and AGRG formulations were investigated in vitro on nerve cell culture and in vivo on 10-mm reconstructed sciatic nerves of 72 rats using different concentrations of agents and completed on a rabbit model of delayed (chronic) complete peripheral nerve injury with a 25-mm gap. Forty rabbits underwent delayed (9 weeks after complete injury of the tibial portion of the sciatic nerve) nerve tube reconstruction of a gap that is 25 mm long. GRG and AGRG groups were compared with autologous and empty tube reconstructed groups. Rats and rabbits underwent electrophysiological and histochemical assessments (19 weeks for rats and 40 weeks for rabbits). Results: Application of AGRG showed a significant increase of about 78% in neurite length per cell and was shown to have the most promising effect on neuronal outgrowth, with total number of neurites increasing by 4-fold. The electrophysiological follow-up showed that AGRG treatment is most promising for the reconstruction of the tibial portion of the sciatic nerve with a critical gap of 25 mm. The beneficial effect of AGRG was found when compared with the autologous nerve graft reconstruction. Thirty-one weeks post the second surgery (delayed reconstruction), histochemical observation showed significant regeneration after using AGRG neurogel, compared with the empty tube, and succeeded in significantly regenerating the nerve, as well as the autologous nerve graft, which was almost similar to a healthy nerve. Conclusion: We demonstrate that in the model of delayed peripheral nerve repair with massive loss defect, the application of AGRG led to a stronger nerve recovery and can be an alternative to autologous nerve graft.